Diagnóstico dos indicadores de desempenho das propriedades leiteiras da região sudoeste do Paraná observando sua evolução - Radaelli, André Luiz Benvenutti (2015)
The dairy cattle have excelled year after year, in the national and global agricultural scenario playing an important role in generating employment and income for producers, especially for those with small farms. With the influence of factors such as increased marketing of milk and milk products and access to the international market, producers who have worked in the activity increased production and improved the technological level of its properties, and contribute to the inclusion of new producers . Thus, this study aims to diagnose performance indicators of farms milk producers in the southwestern region of Paraná. This analysis discusses fundamental questions about the dairy business, therefore, from the review of literature produced on the subject, there was a brief description of the milk production chain in Brazil, Paraná and Paraná Southwest Region. In addition to the bibliographical study, we used as a data collection method the semi-structured interview, applied to a sample of 25 producers in the Southwestern region of Paraná. From the collection of data and performance indicators, it was the current situation of milk production of the surveyed properties, the evolutionary process relative to the start of the activity and future projections. Variations were analyzed regarding milk production, increased estimate of the quantity produced, number of animals, pasture and equipment used factors that have identified the development of the farms studied. The results, among others, suggested great heterogeneity among producers in the region, revealing expansion of production and productivity, as well as advances in genetics of the flock and in management practices.